The Effectiveness of Lavender (Lavendula Augustfolia) and Neroli (Citrus Aurantium) Aromatherapy Inhalation to Decrease Pain Labor: Efektivitas Inhalasi Aromaterapi Lavender (Lavendula Augustfolia) dan Neroli (Citrus Aurantium) terhadap Penurunan Nyeri Pasca Proses Persalinan - Azizah, Nurul; Rosyidah, Rafhani; Machfudloh, Hanik (Universitas Muhammadiyah Sidoarjo, 2020)
Maternal labor will experience almost all body pain, such as painful ribs, stitches, abdominal pain due to uterine contractions, and discomfort in the back due to epidural needles, and this discomfort will last several days and can be overcome by prescription for painkillers. In this study aimed at carrying out non-famacological pain relief therapy, namely by using aromatherapy which is believed to reduce pain, this study tried to compare the effectiveness of lavender and neroli aromatherapy inhalation to decrease post-labor pain. The research method used quasi-experimental that is given aromatherapy lavender (Lavendula Augustfolia) and neroli (Citrus Aurantium) inhalation treatments. The number of respondents was 60 with 1-2 days of normal and postpartum criteria, each group consisted of 30 respondents. Group 1 was held at the Pearl Delta Clinic RB and group 2 in the Karunia RB Clinic. Data were analyzed by univariable by using mean and standard deviation, bivariable with statistical test independent sample T test. The results of this study showed a mean reduction in pain scores on lavender aromatherapy inhalation of 2.36 ± 0.15, whereas in the aromatherapy neroli inhalation group the mean reduction in pain score was 3.03 ± 0.067 with a P value <0.002 indicating a significant relationship. The conclusion of this study is the inhalation of lavender aromatherapy (LavendulaAugustfolia) and neroli (Citrus Aurantium) can reduce the intensity of postpartum pain, but in the aromatherapy neroli inhalation group has a greater pain reduction score than the lavender group.